A Pesquisa Científica no Ensino Médio Técnico Integrado: uma análise no Instituto Federal do Paraná - Soares, Paola Andreza Ávila (2022)
This research brings as scope an analysis of scientific research in the sphere of Professional, Scientific and Technological Education, with a focus on Integrated Technical High School, offered by the Federal Institute of Paraná. This application proposal sought analysis the political pedagogic projects of such courses, the applicability of the teaching concepts of the methodology cientific research, considering the teaching proposal of the research methodology used from the proposal of integrated teaching in the scope Federal Network of Professional, Scientific and Technological. The data collection was through a survey online propose to the teachers, with a objective to identifying their perspective about the relationship between the research cientific and the courses in which they work. The data analysis methodology was based on the use of Discursive Textual Analysis under the purposes and objectives of Federal Law 11.892/2008 with the teachers' reports. The results point to the Federal Network of Professional, Scientific and Technological Education as a public policy of wide dissemination, access and democratization of knowledge, with a lot of encouragement to scientific practice and scientific research in basic education, in the national territory. At the Federal Institute of Paraná, there are a total of 72 integrated Technical High School courses and of this total, between the years 2018 and 2021, 20% of these courses require scientific production as a requirement for formation and, however, does not provide an offer a discipline of scientific research methodology in the curriculum. Therefore, although the reports of the investigated teachers point to benefits about use the cientific research and how important are to the process for the development of the students, their opinion are not consensual, although it is an institutional norm. It points out the need to think about the debate on this theme, on the part of managers and professors who promote the institutional documents of the campuses, in a proposal project between scientific education and technological science.